PENERAPAN SISTEM E – FILLING SEBAGAI PEMEDIASI HUBUNGAN ANTARA SIKAP WAJIB PAJAK DAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI (KPP Pratama Semarang Gayamsari) - Muhamad Reza Mahendra Suhardi; Herry Laksito (Diponegoro Journal of Accounting, 2020)
This study aims to examine the mediating role of adoption of an e – filling in the relationship between attitude toward using and tax compliance of individual taxpayer at KPP Pratama Gayamsari Semarang. TAM (Technology Acceptance Model) defined by Davis is technology acceptance theory that used in this research. Type of research in used a quantitive research approach with data colleting using questionnaires and data analysed using path analysis. Data obtained  from individual taxpayers registered at KPP Pratama Gayamsari Semarang covering Pedurungan, Gayamsari, and Genuk sub-district with close-ended questions were used. E – questionnaires were received 110 and were analysed with the help of SPSS v25. A significant positive relationship was observed between attitude toward use and tax compliance. A significant positive relationship was observed between adoption of an e - filling and tax compliance. The result of examined of the adoption of an e – filling as mediating variable using path analysis indicated that adoption of an e – filling had indirectly effect between attitude toward use and tax compliance of individual taxpayer at KPP Pratama Gayamsari Semarang